THE ASSOCIATION OF GLUTATHIONE TRANSFERASE OMEGA POLYMORPHISMS WITH LABORATORY INFLAMMATORY PARAMETERS IN COVID-19: THE ASSOCIATION OF GСТО1 AND GSTO2 WITH INFLAMMATION IN COVID-19 - Đukić, Tatjana; Stevanovic, Goran; Coric, Vesna; Bukumiric, Zoran; Pljesa-Ercegovac, Marija; Matic, Marija; Jovanovic, Djurdja; Asanin, Milika; Ercegovac, Marko; Ranin, Jovan; Milosevic, Ivana; Simic, Tatjana; et al. (Medical Research, 2022)
Introduction: In a view of important functions of glutathione transferase omega (GSTO) class in redox homeostasis and innate immunity, we proposed that interindividual differences in COVID-19 clinical manifestations might be affected by GSTO1 (rs4925) and GSTO2 (rs156697) polymorphisms. Aim: To assess the potential association of these polymorphisms with biochemical, coagulation and inflammatory laboratory parameters in the group of mild and severe COVID-19 patients. Methods: GSTO1 and GSTO2 single nucleotide polymorphisms were determined by qPCR in 251 samples of COVID-19 patients. Results: Polymorphisms of GSTO1 and GSTO2 affect laboratory biochemical profile of COVID-19 patients. GSTO1*C allele was associated with increased levels of CRP (p=0.035), IL-6 (p = 0.047), D-dimer (p=0.014) and LDH (p=0.002), whereas GSTO2*G allele was associated with CRP (p = 0.033). COVID-19 patients homozygous for variant GSTO1*A allele and GSTO2*G had the highest levels of serum iron (p=0.019, p=0.052, respectively). Conclusion: Our findings regarding the influence of GSTO1 and GSTO2 polymorphisms on inflammation and coagulation parameters might be of clinical importance. In the future, these findings could aid in a more personalized approach for better recognition of patients prone to thrombosis and excessive immune response. Kеywords: COVID-19, polymorphisms, inflammation, GSTO1, GSTO2